Les Catholiques à Constantinople. Galata et les églises de rite latin au xviie siècle - Elisabetta Borromeo (Revue des Mondes Musulmans et de la Méditerranée)
This article suggests some elements for reflection on the catholic presence in the 17th century Galata, suburb of Constantinople. On the base of the accounts of the catholic missionaries and some Ottoman documents (kept in the archives of Saint Peter and Paul’s church in Istanbul), this study examines the legal status of these Catholics, their distribution in the urban space as well as the means they used to expressing their identity.